THU0196 Genome-Wide Trans-Ancestry Meta-Analysis of Herpes Zoster in Rheumatoid Arthritis and Psoriasis Patients Treated with Tofacitinib. (15th July 2016) - Bing, N.; Zhou, H.Y.; Zhang, B.H.; Nagaoka, M.; Valdez, H.; Vincent, M.; Clark, J.D.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of RA. Rates of HZ were higher than seen with other agents used to treat RA in the tofacitinib RA development programme, especially in Japan and Korea. 1 Higher than expected HZ rates were also noted in tofacitinib PsO studies in Japan. Thus, it is important to identify the mechanisms of increased risk of HZ infection for patients (pts) receiving tofacitinib. Objectives: To determine if the increased risk of HZ infection with tofacitinib is associated with genetic risk factors, and whether such factors can inform the mechanisms of increased rate of HZ with tofacitinib and the variation of HZ infection rate across ethnicities. Methods: We performed a trans-ethnic and trans-indication meta-analysis of a genome-wide association study in 5246 tofacitinib-treated pts in RA and PsO Phase 2, 3 and long-term extension (LTE) studies (data cut-off April 2014; LTE ongoing, database not locked), by evaluating ∼8 million genetic variants on HZ event (case vs control) and time to HZ event via logistic and Cox regressions, respectively. Results: After adjusting for age, baseline absolute lymphocyte count, genetically defined ethnicity and concomitant methotrexate use (RA only), we identified 5 loci associated with either increased HZ event rate and/or shorter time to HZ event at a genome-wide significance (p<5x10 –8 ). Two associations were noteworthy based on biological plausibility. A SNP near CD83 (and LINC01108) was associated with increased risk of HZ events (meta-analysis OR=3.7, p=2.1x10 –8 ). Frequency of the risk allele was low (<3%) in Caucasian pts and rare (<0.1%) in Japanese pts. CD83 is expressed on multiple immune subsets, is a marker of dendritic cell maturation and B-cell activation and is down-regulated in dendritic cells by VZV infection, suggesting a plausible mechanism for increased HZ risk in pts treated with tofacitinib. The second SNP was near IL-17RB and was associated with faster rate of HZ onset (meta-analysis HR=3.6, p=7.6x10 –10 ); this was driven by a risk allele common in Japanese pts (∼17% in general Japanese population) but occurring in <0.2% of Caucasian pts. IL-17RB is highly expressed on iNKT2 and iNKT17 cells, whereas iNKT1 cells are IL-17RB negative and dependent on JAK-dependent IL-15. iNKT cell deficiency with low production of IFN-gamma by iNKT cells was linked to disseminated VZV in response to vaccination in 2 case reports, despite generally intact immune systems. Overexpression of IL-25, the ligand for IL-17RB, also led to recurrence of VZV, suggesting that the ratio of iNKT1 to iNKT2 and 17 cells is important. Conclusions: Genetic analysis of ∼5300 pts treated with tofacitinib identified multiple loci associated with an increased risk of HZ. The risk allele of one SNP was significantly more prevalent in Japanese pts. A possible iNKT cell skewing mechanism was suggested and will be evaluated in future studies. References: Winthrop K et al. Arthritis Rheumatol 2014; 66: 2675–2684. Acknowledgement: Previously presented (Bing N et al. Arthritis Rheumatol 2015; 67 (S10): Abstr 566) and reproduced with permission. This study was funded by Pfizer Inc. Editorial support was provided by S Johnson of Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: N. Bing Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, H. Zhou Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, B. Zhang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Nagaoka Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, H. Valdez Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Vincent Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Clark Shareholder of: Pfizer Inc, Employee of: Pfizer Inc